2021
DOI: 10.1007/978-3-030-63693-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Turning Data into Actionable Policy Insights

Abstract: It is becoming clearer that data-supported input is essential in the policy making process. But at which point of the process, and in which format, can data aid policy making? And what does an organisation need to turn data into relevant insights? This paper explores the role of data from two perspectives. In the first part, data and data analysis are situated in the policy making process by mapping them onto the data supported policy making model and highlighting the different roles they can assume in each st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Policymakers are already bombarded with information (Dunlop et al , 2018, p. 11); hence, the idea that they need to leverage large quantities of data seems misleading. Instead, they should be provided with insights from trusted and legitimated sources (Verstraete et al , 2021, p. 74). Accordingly, the use of non-traditional data for policymaking will have to align with the existing public bodies’ mandate and become germane to single policy context dynamics (Durrant et al , 2018; Klievink et al , 2017).…”
Section: Introduction: the Importance Of Non-traditional Data For Pol...mentioning
confidence: 99%
“…Policymakers are already bombarded with information (Dunlop et al , 2018, p. 11); hence, the idea that they need to leverage large quantities of data seems misleading. Instead, they should be provided with insights from trusted and legitimated sources (Verstraete et al , 2021, p. 74). Accordingly, the use of non-traditional data for policymaking will have to align with the existing public bodies’ mandate and become germane to single policy context dynamics (Durrant et al , 2018; Klievink et al , 2017).…”
Section: Introduction: the Importance Of Non-traditional Data For Pol...mentioning
confidence: 99%
“…Our findings in chapter 3 and 4 also specify how adequate different types of data are used in the sustainable urban mobility policymaking process by distinguishing the long-and short-term policy cycle. This adds to Verstraete et al (2021) who shed light on how to use data in the different steps of the policy cycle by emphasizing what approaches could be used to analyze data in each of the steps, based on both scientific literature review and practical case studies. Their work, which was part of EU project PoliVisu (https://www.polivisu.eu/) (Concilio et al, 2021), also found that limited data literacy is the key constraint to successful use of data in urban policymaking, but they did not highlight the distinct role of data in the short-and long-term policy cycle (chapter 4).…”
mentioning
confidence: 99%